Role of bioglass derivatives in tissue regeneration and repair: A review - Gao Yang; Seles Mohan Anne; Rajan Mariappan (Reviews on Advanced Materials Science, 2023)
Bioceramics are significantly contributing in repairing and reconstructing the defective areas of the musculoskeletal system. Bioactive glass is a non-crystalline bioceramic that has been widely used in regeneration due to its extensive bone-forming ability and biocompatibility. The plethora of bioactive glass research has been buried over the years in the area of bone construction in various forms. The composition of the bioactive glass with its network formers and modifier plays a vital role in bone-forming ability and prevents crystallization. The hybrid polymer and metal ion-doped bioactive glass add advantages to bone tissue repair. The development and the challenge during the preparation of bioactive glasses have been discussed in this review. Based on the orthopedic defect, their porous size, volume, and even mechanical properties can be tailored to obtain the desired scaffold combined with the therapeutic delivery of bioactive compounds. Bone tissue engineering is inevitable without the process of osteoinduction, osteoconduction, and osteointegration, and their role in bioactive glass was reported. Bioactive glass is the key contributor to the glass age, and it has been subjected to medicinal applications for tissue repair, regeneration, and therapeutic agent delivery.